EFEKTIFITAS METODE CERAMAH BERVARIASI DALAM PEMBELAJARAN ALQURAN HADIST DI MTS AL WASHLIYAH 47 BINJAI - Hasan, Mat; Hemawati, Hemawati; Sirait, Robin (Tahdzib Al-Akhlaq: Jurnal Pendidikan Islam, 2024)
Abstract. Students' difficulties in understanding the meaning and content of verses in learning Al-Quran Hadith is an obstacle for Al-Quran Hadith teachers at MTs Al Washliyah 47, Binjai City. Al Quran Hadith teachers try to improve their teaching methods by using varied lecture methods, and provide increased student understanding. This research aims to determine the effectiveness of using varied lecture methods in increasing students' understanding in learning Al-Quran Hadith in class VIII MTs Al Washliyah, Binjai City. The method used in this research is a qualitative method with descriptive field studies through interviews. Based on the research results, it is known that the implementation of lecture methods varies by teachers with variations in appearance, namely variations in movements and expressions, variations in voice, silent interludes, gaze contact, concentration of attention and changes in position. The application of the lecture method varies by conditioning the class, delivering the material and providing opportunities to ask questions and ending by providing training on the material. I achieved the afterlife by staying away from materialism, hedonism and consumption, with an average score of 80, an indicator of students' understanding. Keywords: Method, varied lectures, understanding Abstrak. Kesulitan siswa dalam memahami makna dan kandungan ayat dalam pembelajaran Al Quran hadis merupakan kendala guru Al Quran Hadis di MTs Al Washliyah 47 Kota Binjai. Guru Al Quran Hadis mengupayakan memperbaiki metode pengajarannya dengan menggunakan metode ceramah bervariasi, dan memberikan peningkatan pemahaman siswa. Penelitian ini bertujuan untuk mengetahui efektifitas penggunaan metode ceramah bervariasi dalam meningkatkan pemahaman siswa dalam pembelajaran Al Quran Hadis di kelas VIII MTs Al Washliyah Kota Binjai. Metode yang digunakan dalam penelitian ini merupakan metode kualitatif dengan deskriptif studi lapangan melalui wawancara. Berdasarkan hasil penelitian diketahui bahwa pelaksanaan metode ceramah bervariasi yang dilakukan guru dengan variasi penampilan, yakni variasi gerak dan mimik, variasi suara, selingan diam, kontak pandang, pemusatan perhatian dan perubahan posisi. Penerapan metode ceramah bervariasi dengan mengkondisikan kelas, penyampaian materi dan memberi kesempatan bertanya dan diakhiri dengan memberikan latihan tentang materi ku raih kehidupan akhirat dengan menjauhi materialistik, hedonis dan konsumtif, dengan rata-rata nilai 80, menjadi indikatot dalam pemahaman siswa.